A Case of Clostridium Difficile Enterocolitis Succsessfully Treated with Vancomycin Administered Via Long Intestinal Tube - Ishiguro, Seiji; Kobayasi, Ichiro; Matsumoto, Takatoshi; Moriura, Shigeaki; Tabata, Tomotake; Sato, Taichiro (The Japanese Journal of Gastroenterological Surgery, 2002)
We report a case of Clostridium difficile (CD) enterocolitis succsessfully treated with vancomycin (VCM) administered via long intestinal tube. An 82-year-old man was refer to the hospital because of obstructive jaundice. He was diagnosed as hilar cholangiocarcinoma by endoscopic retrograde cholangiography. For acute obstructive suppurative cholangitis, we attempted percutaneous transhepatic bile duct drainage, but failed, necessitating a laparotomy for drainage. RTBD tubes were inserted into the left and right hepatic ducts through the stricture of the hilar bile duct and bile juice was drained extracorporally. On postoperative day 8, excessive diarrhea was observed and toxin A of CD was positive from stool specimens. Oral VCM (2.0g/day) was started, but severe abdominal pain and distension occurred 4 days thereafter. Abdominal X-ray showed paralytic ileus. We inserted a long intestinal tube to administer. The man's condition improved dramatically the next day, and the tube was removed after 6 days. Oral administration with VCM is effective in treating CD enterocolitis, but in paralytic ileus, orally administered VCM does not reach the site of interstinal inflammation, long intestinal tube may thus present a viable alternative in refractory CD enterocolitis.